Raspberry Pi nest cameras: An affordable tool for remote behavioral and conservation monitoring of bird nests. Issue 21 (11th October 2021) - Hereward, Hannah F. R.; Facey, Richard J.; Sargent, Alyssa J.; Roda, Sara; Couldwell, Matthew L.; Renshaw, Emma L.; Shaw, Katie H.; Devlin, Jack J.; Long, Sarah E.; Porter, Ben J.; Henderson, Jodie M.; Emmett, Christa L.; et al.
Abstract: Bespoke (custom‐built) Raspberry Pi cameras are increasingly popular research tools in the fields of behavioral ecology and conservation, because of their comparative flexibility in programmable settings, ability to be paired with other sensors, and because they are typically cheaper than commercially built models. Here, we describe a novel, Raspberry Pi‐based camera system that is fully portable and yet weatherproof—especially to humidity and salt spray. The camera was paired with a passive infrared sensor, to create a movement‐triggered camera capable of recording videos over a 24‐hr period. We describe an example deployment involving "retro‐fitting" these cameras into artificial nest boxes on Praia Islet, Azores archipelago, Portugal, to monitor the behaviors and interspecific interactions of two sympatric species of storm‐petrel (Monteiro's storm‐petrel Hydrobates monteiroi and Madeiran storm‐petrel Hydrobates castro ) during their respective breeding seasons. Of the 138 deployments, 70% of all deployments were deemed to be "Successful" (Successful was defined as continuous footage being recorded for more than one hour without an interruption), which equated to 87% of the individual 30‐s videos. The bespoke cameras proved to be easily portable between 54 different nests and reasonably weatherproof ( 14% of deployments classed as "Partial" or "Failure" deployments were specifically due to the weather/humidity), and we make further trouble‐shooting suggestions to mitigate additional weather‐related failures. Here, we have shown that this system is fully portable and capable of coping with salt spray and humidity, and consequently, the camera‐build methods and scripts could be applied easily to many different species that also utilize cavities, burrows, and artificial nests, and can potentially be adapted for other wildlife monitoring situations to provide novel insights into species‐specific daily cycles of behaviors and interspecies interactions. Abstract : We present a methodological paper focusing on a practical issue, describing a novel and easily constructed field camera system that has been designed (and rigorously tested) for deployment in remote locations with harsh conditions. We describe how the system can be easily adapted for diverse conservation/management and field ecology projects.